Physical Treatments for Alleviating Chilling Injury in Fresh produce - Putri Wulandari Zainal; Daimon Syukri; Irfan Suliansyah; Khandra Fahmy (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Fresh produce has a short shelf-life because the metabolic activity continues after harvest. Low temperature is one of the postharvest technology methods that suppress this activity along storage. Its effects prolong the shelf-life of fruits and vegetables. This method has long been recommended to reduce deterioration during storage so that it can maintain the quality of fruits and vegetables. However, it still has drawbacks such as chilling injury, especially in tropical and subtropical origins that are chilling sensitive. Therefore, another storage method is needed to alleviate chilling injury such as low-temperature conditioning, high-temperature conditioning, and intermittent warming which only use environmental conditioning during storage. The other one has modified atmosphere packaging and controlled atmosphere packaging. They utilize the ideal atmosphere for each fresh product during storage. The treatment proved that it could alleviate chilling injuries such as reduced pitting, flesh injury, failure of mature, scald, peel browning, weight losses, electrolyte leakage, malondialdehyde, respiration rates, production of superoxide radical anion (O₂-) & hydrogen peroxide (H₂O₂), lipoxygenase activity, phospholipase D, phenylalanine ammonia-lyase (PAL), and polyphenol oxidase (PPO). Keywords: Chilling injury, Fresh produce, Intermittent warming, Low temperature, Physical treatment.